2021
DOI: 10.3390/metabo11100657
|View full text |Cite
|
Sign up to set email alerts
|

In Utero Exposure to Persistent Organic Pollutants and Childhood Lipid Levels

Abstract: Animal studies have shown that developmental exposures to polybrominated diphenyl ethers (PBDE) permanently affect blood/liver balance of lipids. No human study has evaluated associations between in utero exposures to persistent organic pollutants (POPs) and later life lipid metabolism. In this pilot, maternal plasma levels of PBDEs (BDE-47, BDE-99, BDE-100, and BDE-153) and polychlorinated biphenyls (PCB-138, PCB-153, and PCB-180) were determined at delivery in participants of GESTation and Environment (GESTE… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…This seems in contrast to the findings of a Spanish cohort including 219 fourteen-year-old children, where no association was found between prenatal PCB levels and levels of HDL-C [ 19 ]. In a cohort of 6–7-year-old children, no associations were found between maternal PCB levels and levels of HDL-C, either [ 26 ]. The latter study reported that maternal PCB-138 was associated with lower childhood levels of triglycerides, LDL-C, and total lipids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This seems in contrast to the findings of a Spanish cohort including 219 fourteen-year-old children, where no association was found between prenatal PCB levels and levels of HDL-C [ 19 ]. In a cohort of 6–7-year-old children, no associations were found between maternal PCB levels and levels of HDL-C, either [ 26 ]. The latter study reported that maternal PCB-138 was associated with lower childhood levels of triglycerides, LDL-C, and total lipids.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, no other studies have been performed on the effects of prenatal exposure to PBDEs and lipid hormone profile at adolescence and, therefore, there are no studies to compare our results with. In a Canadian cohort including 6–7-year-old children, Boutot et al reported that higher in utero BDE-99 exposure was associated with lower childhood levels of triglycerides and non-significantly with higher HDL-C and lower total lipids [ 26 ]. An explanation for the differences between the directions of the associations might be the differences in the age of children included in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a positive association was found between total PBDEs and gestation diabetes mellitus (GDM) in Tehran women (70 cases vs 70 controls) [100]. Another study on 147 mother-children pairs demonstrated that in utero BDE-99 was associated with lower childhood levels of triglycerides, high-density lipoprotein, and total lipids in children's blood at 6-7 years of age [101], suggesting long-lasting metabolic effects of earlylife exposures.…”
Section: Metabolic Disruptionmentioning
confidence: 94%
“…In the general population, PBDE concentrations in blood may reach the nM range [101,135,136], suggesting that in highly exposed individuals, PBDE and their metabolites may disrupt androgenic signaling by direct antagonistic interaction with AR. Additionally, changes in testosterone signaling may result from its decreased production and/or altered hypothalamic-pituitary control.…”
Section: Endocrine Disruption: Testosterone Signalingmentioning
confidence: 99%
“…Concerning the health of future generations, studies on the association of serum PCB levels of pregnant women and pregnancy outcomes have shown a significant association with the neonatal thyroid hormone status [ 110 , 111 ]. The effects on infants might be due to in utero exposure [ 110 , 112 ] or breastmilk consumption [ 113 , 114 , 115 ].…”
Section: Health Impactmentioning
confidence: 99%